Surgical resection and peri-operative chemotherapy for colorectal cancer liver metastases: A population-based study. Issue 2 (February 2016) - Booth, C.M.; Nanji, S.; Wei, X.; Biagi, J.J.; Krzyzanowska, M.K.; Mackillop, W.J.
Abstract: Background: Most literature describing surgery for colorectal cancer (CRC) liver metastases (LM) comes from high volume centres. Here, we report management and outcomes achieved in routine clinical practice. Methods: All cases of CRC in Ontario who underwent resection of LM in 1994–2009 were identified using the population-based Ontario Cancer Registry. Electronic treatment records identified chemotherapy delivery. Temporal trends are described for 3 periods: 1994–1999, 2000–2004, 2005–2009. We describe volume of resected CRCLM as a ratio of incident cases per CRCLM resection. Overall (OS) and cancer-specific survival (CSS) are measured from time of LM resection. Results: 2717 patients underwent resection of CRCLM. Between 1994 and 2009 there was a 78% increase in case volume; from one resection for every 48 incident cases to one resection for every 27 incident cases, p < 0.001. Use of peri-operative chemotherapy increased over study periods from 44% (306/700), to 52% (429/830), to 65% (777/1187, p < 0.001). Chemotherapy utilization rates varied across geographic regions (range 43%–69%, p < 0.001). Post-operative mortality rates at 30 and 90 days were 2.5% and 4.3% respectively. Five year OS during the study periods was 36% (95% CI 32–39%), 40% (95% CI 36–43%), and 46% (95% CI 43–49%) (p < 0.001); CSS was 38% (95% CI 35–42%), 42% (95% CI 38–45%), 49% (95% CI 44–53%) (p < 0.001). The temporal improvement in OS/CSS persisted on adjusted analyses. Conclusions: Outcomes of patients with resected CRCLM in routine practice is comparable to those reported from high volume centres. Survival improved over the study period despite a greater proportion of patients with CRC undergoing liver resection.